2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5627123
|View full text |Cite
|
Sign up to set email alerts
|

Portable and attachable tele-echography robot system: FASTele

Abstract: The purpose of this report is to propose portable and attachable tele-echography robot system: FASTele. Focused assessment with sonography for trauma (FAST) is important for patients who have shock by internal bleeding. However, the patient has little time, and transportation to a hospital may take too long. A system which enables FAST more quickly is required. Therefore, we aim to develop a tele-echography (FAST) robot system that can be used by a paramedic easily for shock patient in ambulance or at injury s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…We purposely constraint the motion of the robot to simulate the 4-DOF kinematic of the PROSIT robot by applying only the velocity vector v to the probe (1). Moreover, in order to automatically keep the contact between the probe and the phantom, we regulated the v z velocity by the independent force control scheme (14) to maintain a f * z = 1 N contact force. In a first experiment, the user performed an exploration of the phantom by tele-operating the rotational velocities of the probe without enabling the visibility assistance mode.…”
Section: A Visibility Assistance Results With An Anthropomorphic Robotmentioning
confidence: 99%
See 1 more Smart Citation
“…We purposely constraint the motion of the robot to simulate the 4-DOF kinematic of the PROSIT robot by applying only the velocity vector v to the probe (1). Moreover, in order to automatically keep the contact between the probe and the phantom, we regulated the v z velocity by the independent force control scheme (14) to maintain a f * z = 1 N contact force. In a first experiment, the user performed an exploration of the phantom by tele-operating the rotational velocities of the probe without enabling the visibility assistance mode.…”
Section: A Visibility Assistance Results With An Anthropomorphic Robotmentioning
confidence: 99%
“…Some of these proposed systems showed the development of dedicated concepts, generally called bodymounted devices, that are usually positioned on the patient's body thanks to the reduced dimensions and their lightweight mechanisms. As an example of the kinematic performances of these concepts, one can refer to [11], [12] for parallel mechanisms and to [13], [14] for serial or hybrid structures. In [15], Nouaille et al showed that, among these structures, a 4 degrees-of-freedom (DOF) light-weight spherical wrist robot is a good candidate to satisfy the strong constraints of mobility, accessibility to any medically isolated place and kinematic performances of the tele-operated device to enable an accurate follow-up of the expert gestures at a distance.…”
mentioning
confidence: 99%
“…The chambers are framed by a two-parts aluminum body (8), (9). The chambers are separated by a flexible PU membrane (10). The upper chamber is covered by a flexible silicone membrane (11) and incorporates the ultrasound probe (12).…”
Section: B Dynamic System Descriptionmentioning
confidence: 99%
“…However, the robot became large size for counter weights and total weight should be increased. On the other hand, a patient-mounted robot has been reported in [5]. The robot is portable, compact in size, and lightweight compared with serial robots, but the robot uses electric motors on patient skin and less backdrivability because of high gear ratios.…”
Section: Introductionmentioning
confidence: 97%
“…Several medical prototype robots for US probe scanning have been developed. For example, robots for teleechography, [3][4][5] robotic (three-dimensional)-ultrasound imaging, [6] and robotic automatic scanning. [7] In [6,7], the robots were designed as a serial-link mechanism.…”
Section: Introductionmentioning
confidence: 99%